2017
DOI: 10.1002/rra.3227
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Proportion of Sediment‐sensitive Invertebrates (PSI) biomonitoring index

Abstract: Sedimentation of river beds is a key pressure impacting riverine ecological communities. Research has identified the need for new approaches to help demonstrate and quantify the impacts of excessive fine-sediment deposition on benthic macroinvertebrate populations. To help meet this requirement, the Proportion of Sediment-sensitive Invertebrates (PSI) methodology was developed and has been in operational use in the United Kingdom for several years. This paper presents a number of case studies, at both national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The differential distribution of traits generally indicates their value for biomonitoring. It is suggested that the trait-based approach can be further explored, with a view to developing trait-informed indices such as the proportion of sensitive invertebrate (PSI) (Extence et al, 2017) and species at risk (SPEAR) (Verberk et al, 2013) models for Afrotropical riverine systems.…”
Section: Resultsmentioning
confidence: 99%
“…The differential distribution of traits generally indicates their value for biomonitoring. It is suggested that the trait-based approach can be further explored, with a view to developing trait-informed indices such as the proportion of sensitive invertebrate (PSI) (Extence et al, 2017) and species at risk (SPEAR) (Verberk et al, 2013) models for Afrotropical riverine systems.…”
Section: Resultsmentioning
confidence: 99%
“…There also exists a number of biomonitoring indices within the UK, where the extent of fine sediment stress can be inferred from the assemblage of benthic macroinvertebrate found instream using biotic indices (e.g. Murphy et al, 2015Murphy et al, , 2017Turley et al, 2016;Extence et al, 2017). Although biomonitoring indices offer a potential way towards setting sediment targets, they lack the explicit link to the causation of elevated fine sediment loads and accumulation and thus, suitable mitigation strategies.…”
Section: Current Approaches To Sediment Targetsmentioning
confidence: 99%
“…A number of biological indices that relate the structural responses of macroinvertebrates to fine sedimentation have been proposed (e.g., Murphy et al, ; Relyea, Minshall, & Danehy, ; Turley et al, ). Extence, Chadd, England, and Naura () evaluate one such biological index, the proportion of sediment sensitive invertebrates. They demonstrate its potential application as a national screening and catchment management tool in the identification of priority areas for sediment management practices and for post‐management appraisals.…”
Section: Physical and Biological Approaches To The Appraisal Of Fine mentioning
confidence: 99%